Development of Fe-Cr-C alloys with high Mn content for bone implant - Kartikasari, Ratna; Kadiman, Sugiarto; Muhfidin, Rivan; Aziz, Ihwanul; Triyono, Triyono (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is to combine the properties of Mn and the advantages of Fe-Cr-C to improve biomaterial compatible characteristics. Three alloys of Fe-Cr-C with compositions of 12 wt. % Mn, 16 wt. % Mn, and 20 wt. % Mn, were investigated. Microstructural analysis was carried out using a scanning electron microscope (SEM), and a Vickers hardness test kit was used to evaluate the hardness. The pin-on-disc method was used for the dry slide wear test, and the corrosion test was carried out using the three-electrode cell polarization method. The hardness value of Fe-Cr-C alloy increased by 28.7 % with the increase of Mn content from 12 wt. % (231.8 VHN) to 20 wt. % (298.4 VHN). The tensile strength value increased by 30.3 % with an increase in Mn content from 12 wt. % (522.69 MPa) to 20 wt. % (680.89 MPa), while the strain value decreased by 30.9 %. However, impact toughness did somewhat decline, from 0.213 J/mm2 at 12 wt. % Mn to 0.169 J/mm2 at 20 wt. % Mn. The wear rate results for Fe-Cr-C 20 wt. % Mn 0.000156 mm3/kg. show a reduction of more than 15 wt. % when compared to Fe-Cr-C 12 wt. % Mn because of an increase in the hard-intermetallic area. Additionally, corrosion resistance improved significantly, with the corrosion rate decreasing from 0.005814 mm/yr at 12 wt. % Mn to 0.001780 mm/yr at 20 wt. % Mn, demonstrating that higher Mn content reduces material degradation in corrosive environments. Based on the experimental results, Fe-Cr-C 20 wt % Mn alloy has the highest mechanical and corrosion resistance of the three types of alloys. Fe-Cr-C with high Mn alloys are promising candidates for application as biomaterials for bone implants by optimizing the Mn content and corrosion resistance